Mango Marketing: Prospects and Challenges in the Sweet World of Business (International Journal of Food and Nutritional Sciences, 2019)
Indians are a peasant country; over two thirds of them rely on agriculture for their livelihood. Since agriculture makes up the majority of the Indian economy, any attempt to plan for economic growth would be pointless if the industry did not expand. A sizeable portion of the horticulture sector in our country is devoted to mango growing. Mango producers have a number of challenges, including underemployment, a lack of funding, and the participation of intermediaries. In general, they are less well-off socially and economically. Since mango farming is a seasonal industry, it is obvious that they are unemployed for around half the year. Pawnbrokers and moneylenders are two middlemen in the market that mango producers are taking advantage of. The majority of farmers are illiterate, thus they are not aware of efficient marketing strategies to advertise their produce. They also don't know about the current pricing patterns in different centers. It is therefore crucial to research the marketing opportunities and problems that the mango growers in the East Godavari district confront. Convenient sampling was used to select 150 farmers from the East Godavari taluk for this study